Poverty Traps of Coastal Women; A Systematic Literature Review Approach - Muspida Muspida; Hendri D. Hahury; Hermi Oppier (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study aims to explore the causes and potential solutions to poverty traps experienced by coastal women. Utilizing a systematic literature review method, the research identifies and synthesizes relevant findings from existing studies. The results reveal that the primary drivers of poverty among coastal women include disparities in educational attainment and limited access to economic resources. These constraints, coupled with restricted employment opportunities, contribute to economic dependency on male family members. Such dependency heightens the risk of domestic violence and reinforces the intergenerational transmission of poverty. To address this issue, the study recommends promoting women’s economic empowerment through entrepreneurship training and improved access to financial capital, which may enhance income generation and reduce economic vulnerability.